2013
DOI: 10.4103/0971-9261.107010
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cysts and tumors in infancy and childhood

Abstract: Aim:Review of the clinical presentation, types (histology), and stages of presentation and overall outcome of ovarian tumors.Materials and Methods:This is a retrospective study. Forty nine girls from 3 days to 12 years were included in the study.Results:Fourteen girls had benign and thirty three had malignant ovarian tumors. One girl had bilateral ovarian non-Hodgkin lymphoma. Dysgerminoma (40%) was the commonest malignant tumor followed by malignant teratoma (16.6%).Conclusion:Pain and abdominal lump are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Although Germ cell tumour was the most common malignant ovarian neoplasm in our study accounting up to 71.1% of all the malignant tumours of the ovary occurring in this age group. While immature teratoma was the most common malignant germ cell tumour in our study, dysgerminoma was most common in the studies conducted by Bhattacharyya, et al and Mukhopadhyay et al [2,15] from India.…”
Section: Discussionmentioning
confidence: 50%
“…Although Germ cell tumour was the most common malignant ovarian neoplasm in our study accounting up to 71.1% of all the malignant tumours of the ovary occurring in this age group. While immature teratoma was the most common malignant germ cell tumour in our study, dysgerminoma was most common in the studies conducted by Bhattacharyya, et al and Mukhopadhyay et al [2,15] from India.…”
Section: Discussionmentioning
confidence: 50%
“…So it is recommended that these cysts should be punctured or removed surgically. 13,14 Zampieri et al, showed a strong correlation between cysts with size more than 5cm and need for surgical management. 15 If a foetal ovarian cyst is diagnosed, serial ultrasound for monitoring of cyst dimensions and echogenicity is advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the asymptomatic, simple or uncomplicated cysts which are <5 cm in size can be observed and regularly monitored for the cyst size using ultrasound until it get resolve completely. It usually MP-2020-331 takes 6-10 months [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Depending on the clinical examination or the postnatal ultrasound method, the surgery can be done in the newborn period or later when cysts becomes symptomatic [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%